USM AND THE STAR LAUNCH SOO EWE JIN SCHOLARSHIP FOR USM JOURNALISM - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
PETALING JAYA, 7 April 2017 The Universiti Sains Malaysia (USM) ViceChancellor, Professor Datuk Dr. Asma Ismail earlier today signed a 'Trust Deed' document together with the Group Managing Director and CEO of The Star Media Group, Datuk Seri Wong Chun Wai and widow of the late Soo Ewe Jin (former Executive Editor, The Star), Madam Lim Fong Lan to symbolise the launch of the Soo Ewe Jin (SEJ) Scholarship for USM deserving students.